Menthone lowers H3K27ac levels to inhibit Fusarium proliferatum growth - Zhang, Li-Yan; Li, Tian-Tian; Liao, Hong-Xin; Wen, Jin-Rui; Nie, Hong-Yan; Xu, Fu-Rong; Liu, Xiao-Yun; Dong, Xian (Frontiers in Microbiology, 2025)
BackgroundThe antifungal properties of essential oils (EOs) and their active constituents have been well documented. Histone acetylation is pivotal in modulating gene expression and influences biological processes in living organisms.ResultsThis study demonstrated that menthone, the primary component of Mentha haplocalyx EO, exhibited notable antifungal activity against Fusarium proliferatum (EC50 = 6.099 mmol/L). The treatment significantly inhibited hyphal growth, reduced spore germination rates from 31.49 to 4.95%, decreased spore viability from 46.88 to 20.91%, and reduced spore production by a factor of 17.92 compared with the control group while simultaneously enhancing cell membrane permeability. However, the direct relationship between menthone and histone acetylation in inhibiting F. proliferatum remains nebulous. Our RNA sequencing (RNA-seq) analysis identified 7,332 differentially expressed genes (DEGs) between the control and menthone-treated groups, 3,442 upregulated and 3,880 downregulated, primarily enriched in pathways related to ribosome biogenesis and energy metabolism. Chromatin immunoprecipitation sequencing (ChIP-seq) analysis revealed that menthone inhibited the growth of F. proliferatum by decreasing H3K27ac levels and interfering with the transcription of energy metabolism-related genes. By integrating the RNA-seq data with the ChIP-seq results, we identified 110 DEGs associated with reduced H3K27ac modification primarily associated with ribosome biogenesis. Menthone affected the growth of F. proliferatum by reducing the expression of ribosome biogenesis-related genes (FPRO_06392, FPRO_01260, FPRO_10795, and FPRO_01372).ConclusionThis study elucidated the mechanism by which menthone inhibits F. proliferatum growth from a histone acetylation modification perspective, providing insights into its application as an antifungal agent to prevent root rot in Panax notoginseng.